2022
DOI: 10.3390/ijerph19148659
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Predictors of Child Body Shame in a Polish and Italian Sample

Abstract: The present study aimed at assessing the predictors (related to the functioning of a parent-child dyad) of child body shame. Therefore, in the main analysis we examined relationships among child body shame, child perfectionism, child body dissatisfaction, parent body shame, parent perfectionism, and parent body dissatisfaction. In our main hypothesis we assumed that higher levels of the abovementioned parent functioning-related variables would be associated with higher child body shame after accounting for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…These results indicate that both body shame and age may contribute to the intensity of appearance-based exercise and positive body image deterioration. The results are consistent with some reports cited in the theoretical introduction, e.g., [ 6 , 18 , 19 ]. It may therefore mean that women in the younger age group feel greater shame about their body, which may be related to the fact that standards of appearance are more intensely internalized by this group, and social pressure to have the “perfect body” is more intense [ 45 , 46 ].…”
Section: Discussion and Summarysupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate that both body shame and age may contribute to the intensity of appearance-based exercise and positive body image deterioration. The results are consistent with some reports cited in the theoretical introduction, e.g., [ 6 , 18 , 19 ]. It may therefore mean that women in the younger age group feel greater shame about their body, which may be related to the fact that standards of appearance are more intensely internalized by this group, and social pressure to have the “perfect body” is more intense [ 45 , 46 ].…”
Section: Discussion and Summarysupporting
confidence: 93%
“…Positive image may be understood as love and respect for your own body expressed, inter alia, through [ 16 , 17 ]: (a) accepting your own body (even if it does not conform to idealized standards of beauty), (b) appreciating the uniqueness of the body and functions it can perform in our lives, (c) feeling comfortable and being happy in relation to your body, (d) the ability and tendency to appreciate the values of one’s body, and not to focus too much on its flaws. It is therefore worth verifying whether the direction of the relationship between body shame and positive body image will be consistent with the outcomes from research on negative body image—i.e., whether a high level of shame will favour a low level of positive body image, e.g., [ 6 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parents represent the most important models for children’s development (Maccoby, 1994 ), and they preeminently influence their children’s attitudes toward body image both directly (e.g., via comments and/or criticism; McCabe & Ricciardelli, 2005 ) and indirectly (e.g., through the expression of their own negative body image; Czepczor-Bernat et al, 2022 ; Domoff et al, 2021 ). For example, Abraczinskas and colleagues ( 2012 ) showed that negative body image (i.e., drive for thinness) and bulimic symptomatology in undergraduate women were related to their parents’ weight- and eating-related comments (see also Vincent & McCabe, 2000 ).…”
Section: The Role Of Parental Influence On Children’s Body Imagementioning
confidence: 99%
“…Despite these relevant findings, when focusing on children’s body shame, research is once again very limited. To the best of our knowledge, the only study investigating the association between parental influence and children’s body shame found that parental body dissatisfaction and perfectionism (mainly from mothers) were positively associated with body shame in children at approximately 13 years of age (Czepczor-Bernat et al, 2022 ).…”
Section: The Role Of Parental Influence On Children’s Body Imagementioning
confidence: 99%